Genotype-by-environment interactions and sexual selection - Hunt, John, 1974-; Hosken, David J. (Wiley Blackwell, 2014)
Sexual selection is recognized as being responsible for some of the most extravagant morphologies and behaviors in the natural world, as well as a driver of some of the most rapid evolution. While Charles Darwin's theory is now a fundamental component of modern evolutionary biology, the impact of genotype-by-environment interactions on sexual selection has thus far received little attention. This book represents the first comprehensive analysis of the role genotype-by-environment interactions play in sexual selection and the potential implications that they have for the evolutionary process.